Status and future scope of plant-based green hydrogels in biomedical engineering. (September 2019) - Mohammadinejad, Reza; Maleki, Hajar; Larrañeta, Eneko; Fajardo, André R.; Nik, Amirala Bakhshian; Shavandi, Amin; Sheikhi, Amir; Ghorbanpour, Mansour; Farokhi, Mehdi; Govindh, Praveen; Cabane, Etienne; Azizi, Susan; et al.
Graphical abstract: Highlights: Hydrogels are very important materials for biomedical applications. Plant-based green hydrogels are briefly discussed. Synthesis of plant-based green hydrogels is summarized in detail. Biomedical applications of plant-based green hydrogels are highlighted. State-of-art applications of some of the green hydrogels are briefly presented and discussed. Abstract: Hydrogels are the most iconic class of soft materials, and since their first report in the literature, they have attracted the attention of uncountable researchers. Over the past two decades, hydrogels have become smart and sophisticated materials with numerous applications. This class of soft materials have been playing a significant role in biomedicine due to their tunable and often programmable properties. Hydrogels from renewable polymers have been popularized in biomedical applications as they are often biocompatible, easily accessible, and inexpensive. The challenge however has been to find an ideal plant-based hydrogel for biomedicine that can mimic critical properties of human tissues in terms of structure, function, and performance. In addition, natural polymers can readily be functionalized to engineer their chemical and physical uproperties pertinent to drug delivery and tissue engineering. Here, the most recent advances in the synthesis, fabrication, and applications of plant-based hydrogels in biomedical engineering are reviewed. We cover essential and updated information about plants as green sources of biopolymers for hydrogel synthesis, general aspects of hydrogels and plant-based hydrogels, and thorough discussion regarding the use of such hydrogels in the biomedical engineering area. Furthermore, this review details the present status of the field and answers several important questions about the potential of plant-based hydrogels in advanced biomedical applications including therapeutics, tissue engineering, wound dressing, and diagnostics., etc.